Corporate Social Responsibility (CSR) dalam Embiayaan Pembangunan Non APBN - Nurdin Ardalepa (Jurnal Syntax Admiration, 2023)
Corporate Social Responsibility (CSR) as a form of company responsibility towards the environment and society by protecting and contributing to the community. The implementation of CSR is driven by market pressure and legal regulations. This research uses a descriptive-analytical method with a qualitative approach by collecting data through literature studies and document analysis related to CSR and its implementation in the context of companies and governments. CSR can assist the government in addressing budget limitations in socio-economic development. CSR programs, such as education, can contribute to sustainable development and improve community welfare. An example of a government-company partnership is the training program provided by JNE to micro-business owners in Jember, aimed at developing their businesses in the digital era. JNE also has CSR programs focused on environmental preservation, community empowerment, and education. The implementation of CSR not only provides financial benefits to the company but also contributes to the surrounding environment and enhances the company's reputation.